Comparative genomics reveals environmental adaptation differences between Cronobacter species. (September 2021) - Qin, Xue; Wang, Hao; Miao, Chao; Yang, Xinyan; Zhang, Yanming; Feng, Jing; Forsythe, Stephen J.; Man, Chaoxin; Jiang, Yujun
Graphical abstract: Highlights: Whole-genome comparative analysis was performed on 27 Cronobacter genomes. Cronobacter spp. has genetic diversity and strong environmental adaptability. 97.35% of the core genes are contributed to substrate transport and metabolism. The study improves our understanding of gene function in Cronobacter spp. Abstract: The genus Cronobacter is an opportunistic food-borne pathogen which is able to adapt to diverse environments and shows considerable genetic diversity. Genomic analysis can be used to reveal the variation across the genus with respect to virulence, drug resistance and factors involved in horizontal gene transfer mechanisms, such as integrons, conjugative plasmids, and recombinases. In this study, whole-genome comparative analysis of 27 Cronobacter genomes (12 existing and 15 newly assembled genomes) was performed. A total of 110, 010 protein-coding genes were grouped into 11, 262 clusters, including 2637 core genes, 4814 strain-specific genes and 3811 dispensable genes. Clusters of Orthologous Groups (COG) analysis indicated that 97.35% of the core genes were for substrate transport and metabolism, and the antibiotic resistance genetic determinants were classified into 136 antibiotic resistance ontologies (AROs). A total of 80 genomic islands (GIs) were identified which contained several type VI secretion system gene clusters, and these were likely to have been acquired by horizontal gene transfer. This study has generated a comprehensive characterization of the genus Cronobacter, leading to a better understanding of the mechanisms and ecological functions among the genome features, speciation, and environmental adaptation strategies.